Talking in class : new entrant teachers' beliefs about oral language : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education (Special Education), Massey University - McDonald, Shona (Massey University, 2005)
While oral or spoken language is a primary medium for teaching and classroom communication, there is an absence of literature that relates to the beliefs teachers have about oral language. This study aims to document and discuss seven teachers' beliefs about oral language. To do so, the recording and transcription of the teachers' beliefs about the development of children's oral language, including the strategies and programmes used to assess and promote it in new entrant classrooms, is undertaken. Later, following a period of reflection, each teacher outlines the changes or affirmations to their earlier beliefs, assessments, programmes or teaching strategies that they have considered or implemented. While this study documents the teachers' beliefs, it also discusses them in light of their implications for teaching and learning. In particular, the findings suggest the emergence of a literacy paradigm that includes reading, written and oral language, and within which the teachers view oral language primarily as a conduit to the promotion of reading. Although the teachers discuss how the engagement of learners with and through reading is actively promoted, oral language and its potential to engage five-year-olds in classroom communications, meaning making and learning is not promoted.
Keywords: New Zealand; Children - Language; English language -- Spoken English; Study and teaching (Primary); Oral communication